Trends in the epidemiology of diabetic foot and lower limb amputations in Russian Federation according to the Federal Diabetes Register (2013–2016) - Gagik R. Galstyan; Olga K. Vikulova; Michail A. Isakov; Anna V. Zheleznyakova; Alexey A. Serkov; Daria N. Egorova; Ekaterina V. Artemova; Marina V. Shestakova; Ivan I. Dedov (Сахарный диабет)
BACKGROUND: The epidemiological study of diabetic foot (DF) is very important because of high risk lower limbs amputations in patients with diabetes mellitus (DM). AIMS: The aim of the study was to evaluate the DF prevalence in adult patients with type 1 (T1) and 2 (T2) diabetes in Russian Federation for period 2013–16years. METHODS: We have used the database of the Russian Federal Diabetes register, 81st regions included in the online register. Indicators were estimated per 10,000 adult DM patients (>18years). RESULTS: In 2016, the prevalence of DF in RF was T1 4,7%, T2 1,9%, with marked interregional differences: 0,15–19,9%, 0,07–10,3%, respectively. The DF prevalence in RF decreased: T1 506,3→473,6, T2 214,60→194,8. The incidence of new DF cases/per year was stable in adults with T1: 20,8→20,4/; increased in T2 13.2→14.2. The mean age of DF diagnosis increased by 2years for both DM types. The average DM duration of DF determine increased T1 15.4→19.0years, T2 7.4→10.1years. Proportion of DF forms: neuropathic with trophic ulcer 41.6%, neuropathic form (Charcot's foot) 17.9%, the neuroischemic 28.3%, ischemic 12.2%, in T2: 41.6%, 7,4%, 32,4%, 18,5%, respectively. The amount of new cases of amputations/per year in dynamics: T1 10,5→12,4, T2 9,6→10,9, with marked interregional differences 0.13–2.9% in T1, 0.04-6.0% in T2. The mean DM duration before amputation increased in T1 18.4→21.3years, in T2 9.1→9.9. The average amputation age: T1 51.7years, T2 66.2years. There was marked decrease in proportion of major amputations: T1 43,6→37,0%, T2 52.2→45.5 by redistribution in one toe amputations T14,0→10.0%, in T22,8→ 9.1%. CONCLUSIONS: The dynamic of new DF cases in adult patients in Russian Federation is stable at T1, in T2 tends to increase. The interregional differences in frequency of DF and amputations may be due to differences in the quality of specialized care, the lack or shortage of diabetic foot cabinets, treatment of patients with DF in general surgical practice in a number of regions, which is recognized as a less effective strategy. A positive fact that proportion of high amputations declines, DF develops in later age and longer diabetes duration, that may reflect the increasing effectiveness of preventive lower limbs in diabetes.